DISENTANGLING THE SIGNIFICANT OF IMPROVISATIONAL BEHAVIOR ON WOMEN ENTREPRENEURS’ BUSINESS SUCCESS (Journal of Technology and Operations Management, 2019)
Previous research indicates that improvisation as deliberate extemporaneous composition and execution of novel action is an important matter for any business to be successful. The present article seeks to advance the theoretical knowledge on the influence of improvisation behavior on business success, particularly among women entrepreneur by reviewing and synthesizing available research into a conceptual framework that the relationship of the selected variables. Based on the arguments in this article, a proposition was developed to refine our understanding of the relationship between improvisation and business success. Finally, theoretical and practical implication were discussed.